Electron Spin-Dependent Electrocatalysis for the Oxygen Reduction Reaction in a Chiro-Self-Assembled Iron Phthalocyanine Device - Zagal-Moya, J; Zagal-Moya, J; Aspee-Lamas, A; Ponce-Hormazabal, I; Barrías-González, P; Mura-Mardones, F; Scarpetta-Pizo, L; Scarpetta-Pizo, L; Venegas-Toledo, R; Onate, R (John Wiley and Sons Inc, 2024)
The chiral-induced spin selectivity effect (CISS) is a breakthrough phenomenon that has revolutionized the field of electrocatalysis. We report the first study on the electron spin-dependent electrocatalysis for the oxygen reduction reaction, ORR, using iron phthalocyanine, FePc, a well-known molecular catalyst for this reaction. The FePc complex belongs to the non-precious catalysts group, whose active site, FeN4, emulates catalytic centers of biocatalysts such as Cytochrome c. This study presents an experimental platform involving FePc self-assembled to a gold electrode surface using chiral peptides (L and D enantiomers), i.e., chiro-self-assembled FePc systems (CSAFePc). The chiral peptides behave as spin filters axial ligands of the FePc. One of the main findings is that the peptides′ handedness and length in CSAFePc can optimize the kinetics and thermodynamic factors governing ORR. Moreover, the D-enantiomer promotes the highest electrocatalytic activity of FePc for ORR, shifting the onset potential up to 1.01 V vs. RHE in an alkaline medium, a potential close to the reversible potential of the O2/H2O couple. Therefore, this work has exciting implications for developing highly efficient and bioinspired catalysts, considering that, in biological organisms, biocatalysts that promote O2 reduction to water comprise L-enantiomers. © 2023 Wiley-VCH GmbH.